Separable Words in Modern Chinese and Their Acquisition and Pedagogy Relating to Thai Learners - Lin, Caijun (Journal of Sinology (วารสารจีนวิทยา), 2012)
In modern Chinese, there is a special linguistic unit called Separable Word. Its grammatical status has received special concern as a unique Chinese phenomenon. Different aspects of Separable Word have been studied by many scholars. However, problems, such as “What is the grammatical attribute of Separable Word?” and “What are its distinctive properties?”, are still being debated on. Meanwhile, with the frequent use of Separable Word by those who learn Chinese as a foreign language, various kinds of errors occur, caused by its special linguistic nature. In the field of teaching Chinese as a second language, it is difficult both to learn and to teach Separable Word. Similar problems also occur among Thai learners who study Chinese. This article firstly discusses grammatical attributes and distinctive properties of Separable Word. Its theoretical issues will be probed as fundamental knowledge. Then based on the questionnaire, the acquisitional sequence and the developmental process of Thai students learning Separable Word, as well as the condition, type and causes of errors among Thai students are summarized and analyzed. Finally, corresponding teaching strategies, which are directed to Thai students and their causes of errors, are given at the end of this article.